Influence of sealing of the screw access hole on the fracture resistance of implant-supported restorations - Pereira, Rodrigo de Paula [UNESP] (2016)
The purpose of this study was to assess the influence of sealing of the screw access hole (SAH) on the fracture resistance of metal-ceramic implant-supported restorations. UCLA abutments were used to make 30 implant-retained mandibular molar restorations and divide equally into three groups: Group SRS: screw-retained restorations with SAH sealed; Group SRNS: screw-retained restorations with SAH not sealed; Group CR: cement-retained restorations. The following protocol was adopted to restore the SAH: the ceramic surface of the SAH was air-abraded with aluminum oxide; etched with 10% hydrofluoric acid; a silane coupling agent and a bonding agent were applied; cotton pellets were used as filling material and P-60 resin composite as restoring material. The cement-retained restorations were cemented with Rely-X U100. A metal rod with a spherical tip of 6.0 mm diameter was used to apply a vertical static load, simultaneously on the buccal and lingual incline cusps, at a crosshead speed of 0.5 mm/min until the fracture of the specimens. Data were analyzed using one-way ANOVA and Dunnet test (p<0.05) for multiples comparisons. The mode of failure was evaluated by a scanning electron microscopy (SEM). No significant difference between screw-retained restorations was found. The highest mean fracture resistance values were observed with CR group. Therefore, it was shown that SAH sealing did not influence the fracture resistance of the screw-retained restorations